An Android-Based Game for Improving Students’ English Literacy in Targeted School of Kampus Mengajar - Yusniarsi Primasari; Supriyono; Yayuk Widyastuti; Hesty Puspita Sari (JEELS (Journal of English Education and Linguistics Studies), 2025)
GEMOY (Gleaming English Game for Youth) is an Android-based educational game designed to enhance English literacy among students of Kampus Mengajar program in Trenggalek. This study aims to develop interactive and engaging activities through an Android-based to improve students' literacy levels. Fifty students at the eighth grade in two of junior high schools were equally divided into an experimental group and a control group. Three media validators and three material validators were involved in validating the game. Questionnaires and test were used to collect the data and analyzed using descriptive and Independent T-tests. The findings revealed that the media validation and material validation were valid and the score showed high improvement. The t-value was -51.187. It indicates that there was a significant difference. Based on the result, an important implication of implementing the game in Kampus Mengajar program demonstrates its potential to support educational initiatives and improve students’ literacy competence proven by the significant improvement of the process.